The Rock Cook Wrasse Centrolabrus exoletus Aims to Clean - Morado, Nadia; Mota, Paulo G.; Soares, Marta C. (Frontiers in Ecology and Evolution, 2019)
Cleaning behaviour between teleost fish in the marine environment is known to be a classic example of mutualistic cooperation, in which cleaners and their so-called clients exchange benefits. These mutualisms occur globally. However, studies of cleaning interactions in temperate regions are scarce compared with studies in the tropics. Here we focused on the rock cook, Centrolabrus exoletus, a wrasse present in the North-East Atlantic, considered to be the main cleaner inhabiting the coast of Portugal, although little is known about its ecology and behaviour. We found that these cleaners attended clients in specific locations while others were roaming freely, leaving open the question of which strategy cleaners preferentially use. Interestingly, interactions were initiated more often by clients and terminated more often by cleaners, suggesting that the intake of parasites are the cleaner’s primary interest, which was confirmed by the analysis of their diet, mostly composed of gnathiidae parasites. Moreover, this honesty-based relationship between these cleaners and their clients, calls for a re-interpretation of the very meaning of client-jolts (abrupt movements in response to cleaner mouth touch) since interactions with client jolts lasted longer than interactions with no jolts. This study provides new and important evidence on the mutualistic relationship between C. exoletus and its clientele, thus contributing to a better understanding of the behavioural ecology of this cleaner fish system.